A spectral approach on mineralogy and geochemistry of garnet skarns in Arc-Type granitoids - Sasmaz, Ahmet; Kilic, Ayse Didem; Akgul, Bunyamin; Sasmaz, Bilge (Pergamon-Elsevier Science Ltd, 2023)
Garnets that common constituent of skarn type iron deposits are wide ranges of chemical compositions, and they are also important as a semi-gemstone mineral. This study has been investigated garnets and inclusions of its formed in contacts of Pertek granitoid and Keban marble by using a combination of multiple techniques including Raman spectrum, electron microprobe, petrography and LA-ICP-MS. The main mineral assemblage observed in the skarn formation is diopside, garnet, quartz, magnetite, calcite and pyrite. The garnets are in size between 1 and 7 cm and have reddish, greenish and light-dark brown colour. The compositions of the garnets are mainly grossular-andradite, andradite-grossular, less grossular and andradite. Increased porosity and horizontal flow of hydrothermal fluids during metasomatism resulted in the formation of garnets of different sizes. Raman spectroscopy studies on garnets show to be that the idiomorphic and semi-idiomorphic garnets are predominantly grosular, andradite and uvarovite in the core. Raman spectroscopy studies on garnets showed to have predominantly grossular, andradite and uvarovite composition in the core of the idiomorphic and semi-idiomorphic garnets. As for the rare earth element (REE) analysis and distribution model, the chondrite-normalized REE patterns of all garnets in the study area have similar trends and generally in the right-slopping shape depleted in HREE and enriched in LREE, mostly controlled by adsorption. High Fe2O3, CaO and MgO contents may cause to high mobility during skarn formation associated with contact metamorphism and cation ex-change via hydrothermal fluids (eg uvarovite in the core). All garnets have generally positive Ce and positive Eu anomalies. These results suggest that the garnets in the studya area formed in conditions showing increase in pH and high oxygen fugacity or decrease in temperature in the source of the hydrothermal fluids.
Keywords: Raman imaging; Geochemistry; ICP-MS; Fluid inclusions; Petrology; REE